Utilization of digital technology in marketing agribusiness products - Tri Waluyo (Jurnal Multidisiplin Sahombu, 2024)
With the rapid growth of digital technology, agribusiness as a major sector in the global economy needs to take advantage of this innovation to increase competitiveness and face the challenges of an ever-changing market. This research aims to investigate the impact of using digital technology in increasing the efficiency and effectiveness of marketing agribusiness products. This research uses a qualitative approach with descriptive methods. The research results show that the use of technology in the agricultural sector has a significant positive impact. Mobile applications, agriculture-specific e-commerce platforms, and social media expand farmers' access to markets and increase the visibility of agricultural products. Geographic Information Systems (GIS) help map and monitor agricultural land, while the Internet of Things (IoT) provides real-time information about environmental conditions and plant or animal health. Digital marketing and blockchain techniques increase transparency and consumer trust in agricultural products. Overall, technology integration brings positive change, increases operational efficiency and supports sustainable growth in the agricultural sector.